2022
DOI: 10.1139/cjpp-2021-0299
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic metabolic effects of carvedilol in high-fructose, high-fat diet–fed mice: implication of β-arrestin2 pathway

Abstract: We aimed to investigate the acute and chronic effects of carvedilol on insulin resistance in high-fructose, high-fat diet (HFrHFD)-fed mice and the implication of β-arrestin2 pathway. The acute effect of carvedilol (10 mg/kg, i.p.) on glucose tolerance and hepatic lipid signaling in normal and insulin resistant mice was investigated. Then, the chronic effect of carvedilol on insulin resistance and dyslipidemia in HFrHFD-fed mice was examined. Changes in β-arrestin2 and its down-stream signals in liver, skeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…Moreover, abnormal liver lipid metabolism is related to insulin resistance. Multiple studies have shown that excessive sugar intake leads to impaired glucose tolerance and insulin resistance [42,43]; this was consistent with the results of the current study. Wu et al showed that the PC water extract could improve the tolerance of mice to sucrose and glucose [44].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, abnormal liver lipid metabolism is related to insulin resistance. Multiple studies have shown that excessive sugar intake leads to impaired glucose tolerance and insulin resistance [42,43]; this was consistent with the results of the current study. Wu et al showed that the PC water extract could improve the tolerance of mice to sucrose and glucose [44].…”
Section: Discussionsupporting
confidence: 93%